Engage more, achieve less? the relationship between student engagement and academic achievement among juvenile delinquents at Malaysia correctional institutions - Chin, Wei Mun; Ahmad, Nor Aniza (Human Resource Management Academic Research Society, 2019)
Student engagement has vital role to play and can profoundly affecting students’ learning progress. A sound body of literature found student engagement is positively correlated with academic achievement and assume the underlying relationship implied student engagement lead to improvement of educational outcomes. The contemporary studies of student engagement are focused on aiming to enhance learning and teaching particularly in higher education level. Furthermore, the center attention of literature focused on secondary and university to examine the relationship between student engagement and academic achievement. However, very few studies were found on juvenile delinquents at correctional institutions. To bridge the research and knowledge gap, present study was took place at 4 correctional institutions (Integrity School and Henry Gurney School) under Malaysian Prison Department. The present study adopted multi-stage sampling, in which purposive sampling was employed as the targeted samples were juvenile delinquent students. Meanwhile, two-stage cluster sampling was adopted for the sample randomization, and preserved representative of the population. The present study was conducted on 154 juvenile delinquent students at these correctional institutions through self-report survey questionnaires. Finding from correlation analyses indicated significant relationship found between student engagement and levels of academic achievement. In addition, regression analyses revealed behavioral engagement has significant influence on juvenile delinquent student academic achievement. The study has implications on the role of teacher at correctional institutions, and the effectiveness of current practice pedagogy. Teachers may practice more on student centered learning due to the diversity of students’ background.